Equality-Based Inclusive and Transformational Leadership Style Gender: Study of Khofifah Indar Parawansa as Governor of East Java - Anisa Rachmadini; Syffa Aprilia; Audya Shalma Alfia Devita; Yurika Setiadi; Intan Taufik; Muhamad Farel Alfarizy Gunawan (Majapahit Journal of Islamic Finance and Management, 2025)
This study aims to analyze the inclusive and transformational leadership styles based on gender equality implemented by Khofifah Indar Parawansa in her leadership as the Governor of East Java for the 2025–2030 period. Amid the dynamics of regional development that demand the participation of all societal groups, leadership styles that are responsive to gender equality issues are essential to ensure the realization of social justice and equitable welfare. Using a descriptive qualitative approach through literature review and documentation methods, this article examines the characteristics of Khofifah's leadership, which emphasizes openness, participation, and empowerment of vulnerable groups, especially women. The analysis reveals that Khofifah implemented innovative policies such as the Gender-Responsive Development Planning Forum (Musrenbang Gender), the “Women- and Child-Friendly Village” program, and “Jatim Puspa” (East Java Women's Business Empowerment), which have proven effective in increasing women's participation across various sectors. Additionally, her transformational leadership style is reflected in the strategic program "Nawa Bhakti Satya," aimed at building a more inclusive, just, and sustainable social system. This study concludes that the combination of inclusive and transformational leadership based on gender equality significantly contributes to creating effective, responsive, and equitable regional governance.